PERSEPSI MASYARAKAT TERHADAP KEBIJAKAN POLITIK DI KOTAMADYA MEDAN - PIN PIN . (LP2MTBM MAKARIOZ, 2020)
In the world of politics, the role of political ethics cannot be ignored. This is related to, political morality is useful to investigate what constitutes good and bad, virtue, legal validity, truth of conscience, political moral obligations and so on. The reality of the problem faced in political culture is the gap between Political interference and the bureaucrat's (Administrator) independence regarding service management to the community. Then, there are attitudes and behaviors that are